Untersagung des Führens von Fahrrädern im Straßenverkehr. VG Neustadt a.d.W., Beschluss vom 16.3.2005 - 3 L 372/05. - (:unkn) unknown (Beck, 2005)
StVG § 3; VwGO §§ 44, 44 a, 80,123; FeV §§ 3, 11, 13, 46, 70.
Keywords: Straßenverkehr; Individualverkehr; Kraftfahrzeug; Fahrrad; Verkehrsverhalten; Verkehrsteilnehmer; Alkoholkonsum; Verkehrsdelikt; Fahrerlaubnis; Fahrverbot; Eignungsbeurteilung; Fahreignung